LAUGHTER THERAPY REDUCES ANXIETY IN FIRST YEAR STUDENTS OF STIKes SANTA ELISABETH MEDAN IN 2018 [LAUGHTER THERAPY MENURUNKAN ANSIETAS MAHASISWA TINGKAT I STIKES ELISABETH MEDAN TAHUN 2018] - Mestiana Br Karo; Lindawati Simorangkir; Lestariani Gea (Universitas Pelita Harapan, 2020)
Anxiety is a reaction that anyone can experience. Excessive anxiety will hinder a person's function in his life. Students often experience anxiety, as a result of psychosocial factors, where students do not respond appropriately to stressors, for example, new environmental situations. Laughter therapy is a powerful antidote to stress, illness and conflict. The purpose of this study was to determine the effect of child therapy on the anxiety of first-year students of STIKes/Health Institute of Santa Elisabeth Medan in 2018. The research design applied One Group Pre-Post Test Design. The sampling technique was selected using quota sampling, with a total sample of 63 people. The results of the study revealed that the average anxiety level of the students was 1.83 before being given the laughter therapy. After the laughter therapy, the average of students’ anxiety level decreased into 0.98. The Wilcoxon test showed the comparison score before and after the therapy, with p value 0.0001 (p <0.05). This also means that there was an effect of laughter therapy on the anxiety of students at STIKes Santa Elisabeth Medan in 2018. From the research results, it is expected that students should experience the laughter therapy to reduce their anxiety and manage to more calm and relaxed.BAHASA INDONESIA Ansietas adalah reaksi yang dapat dialami siapapun. Rasa cemas yang berlebihan akan menghambat fungsi seseorang dalam kehidupannya. Mahasiswa sering mengalami cemas, akibat dari faktor psikososial, dimana mahasiswa tidak merespon secara tepat terhadap stressor misalnya terhadap situasi lingkungan yang baru. Laughter therapy atau terapi tawa merupakan penangkal stres, sakit dan konflik yang kuat. Tujuan penelitian ini untuk mengetahui pengaruhlaughter therapy terhadap ansietas mahasiswa tingkat I STIKes Santa Elisabeth Medan Tahun 2018. Desain penelitian menggunakan rancangan One Group Pre-Post Test Design. Teknik pengambilan sampel dipilih dengan menggunakan quota sampling, denganrjumlah sampel sebanyak 63 orang. Hasil penelitian sebelum diberikan laughter therapy, rata-rata tingkat ansietas 1,83. Kemudian setelah diberikan laughter therapy terdapat penurunan menjadi 0,98. Uji statistik yang digunakan adalah uji Wilcoxon dengan nilai p value = 0,0001 (p < 0,05) yang berarti ada pengaruh laughter therapy terhadap ansietas mahasiswa tingkat I STIKes Santa Elisabeth Medan tahun 2018. Dari hasil penelitian di harapkan mahasiswa dapat melakukan laughter therapy sehingga dapat mengurangi kecemasan yang dialami dan membuat lebih tenang dan rileks.